(3GdfXQjI GdYGeI ddSdWI GdJbOjQjI ddbGVj GdLfGFj (B: s (3OQGSI ebGQfI (B/ s - (3aGQS efGMi SYhO GdeWjQis; (3YeQ eMeO SGde (B: s ((3GdbGgQI (B: s, 2013)
(3GdSdWI GdJbOjQjI ddbGVj GdLfGFj JfUH aj GdCSGS Ydi GdJbOjQ h GdehGRfI Hjf GdCOdI GdeYQhVI Ydjg(B: (3h Pdc HZQV GSJLdGA hLg GdMbjbI(B: (3XgQ HhVhM eOi CgejI GdEKHGJ GdLfGFj aj gPG GdUOO(B: (3MjK JJVM gPg GdCgejI aj GdOhQ GdEjLGHj ddbGVj aj GdHMK Yf GdMbjbI(B: (3aGdbGVj GdLfGFj dG jcJaj HeLQO ehGRfI GdCOdI GdJj jbOegG GdNUhe(B: (3h EfeG Ydjg OhQ EjLGHj jaQV Ydjg GdJMQj Yf GdMbjbI h GdcTa YfgG; Pdc Cf GdLQjeI hGbYI JfJej Edj GdeGVjs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2013s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdELQGAGJ GdLfGFjIs; (3JSHjH GdCMcGes; (3SdWI GdbGVi GdLfGFis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3cdjI GdMbhbs